2014
DOI: 10.1371/journal.pone.0102343
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound Characterization of Tumor Cell Death: Ultrasound-Stimulated Microbubbles for Radiation Enhancement

Abstract: The aim of this study was to assess the efficacy of quantitative ultrasound imaging in characterizing cancer cell death caused by enhanced radiation treatments. This investigation focused on developing this ultrasound modality as an imaging-based non-invasive method that can be used to monitor therapeutic ultrasound and radiation effects. High-frequency (25 MHz) ultrasound was used to image tumor responses caused by ultrasound-stimulated microbubbles in combination with radiation. Human prostate xenografts gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Indeed we have previously reported that acute (90 min) activation of AMP-activated protein kinase (AMPK), mimicking conditions that occur during metabolic stress, results in significant changes to the cell surface proteome [ 53 ], largely as a result of changes in membrane traffic. USMB is being combined with clinical cancer treatment methods such as radiotherapy and chemotherapy as a means of enhancing treatment effectiveness and safety [ 9 , 10 , 54 56 ]. Hence, the broad regulation of CME by USMB treatment may also effect large, systematic reprogramming of the cell surface proteome that may have implications for the use of USMB in combination therapy to treat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed we have previously reported that acute (90 min) activation of AMP-activated protein kinase (AMPK), mimicking conditions that occur during metabolic stress, results in significant changes to the cell surface proteome [ 53 ], largely as a result of changes in membrane traffic. USMB is being combined with clinical cancer treatment methods such as radiotherapy and chemotherapy as a means of enhancing treatment effectiveness and safety [ 9 , 10 , 54 56 ]. Hence, the broad regulation of CME by USMB treatment may also effect large, systematic reprogramming of the cell surface proteome that may have implications for the use of USMB in combination therapy to treat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Kim et al . showed the relationship between cell fragmentation and QUS; demonstrating a 17-fold increase in cell fragmentation relative to a change in the mid-band fit and 0-MHz Intercept (7.0 ± 4.1 dBr and 15.4 ± 2.5 dBr, respectively) [ 7 ]. In photodynamic-treated (PDT) melanoma treatments, Banihashemi and colleagues used high frequency ultrasound (26 MHz) to detect apoptotic cell death, and showed a statistically significant correlation between QUS changes and cell death up to 24 hours after PDT treatment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, at higher acoustic pressures, ultrasound can cause microbubble disruption through cavitation and oscillations. Previous studies have shown that when bubbles are introduced to the tumor vasculature and insonified using high mechanical indices, the mechanical forces can perturb endothelial cells within the vessels themselves [ 7 ]. There is evidence to support that this disruption initiates cell death signalling similar to radiation response mechanisms, and can lead to additive tumor damage [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, acute vascular shutdown and significant tumor cell death is observed [33,34], indicating that tumor cell death is secondary to endothelial cell death. Several in vivo studies have also indicated the effectiveness of this therapy in treating xenograft tumors in murine models, including breast, prostate liver, and bladder [21,22,[35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%